Ileal Microbiota Alters the Immunity Statues to Affect Body Weight in Muscovy Ducks - Fu, Zixian; Yang, Hua; Xiao, Yingping; Wang, Xiaoli; Yang, Caimei; Lu, Lizhi; Wang, Wen; Lyu, Wentao (Frontiers in Immunology, 2022)
The ileum is mainly responsible for food absorption and nutrients transportation. The microbes in its intestinal lumen play an essential role in the growth and health of the host. However, the association between the microbes in the ileum and body weight and immunity is still unknown. In this study, we used Muscovy ducks as an animal model to investigate the relationship between the ileal microbes and body weight as well as immunity, and further explore the potential mechanism in it. The ileum tissue and ileal contents of 200 Muscovy ducks were collected for mRNA extraction and real-time PCR, as well as DNA separation and 16S rRNA gene sequencing. With body weight being ranked, the bottom 20% (n = 40) and top 20% (n = 40) were set as the low and high groups, respectively. Our results showed that in the ileum of Muscovy ducks, the Bacteroides, Firmicutes, and Proteobacteria were the predominant phyla with 10 most abundant genera, namely Candidatus Arthromitus, Bacteroides, Streptococcus, Vibrio, Romboutsia, Cetobacterium, Clostridium sensu stricto 1, Terrisporobacter, Escherichia-Shigella, and Lactobacillus. We identified Streptococcus, Escherichia-Shigella, Candidatus Arthromitus, Bacteroides, Faecalibacterium, and Oscillospira were closely correlated to the growth of Muscovy ducks. Streptococcus and Escherichia-Shigella were negatively related to BW, while Candidatus Arthromitus, Bacteroides, Faecalibacterium, and Oscillospira were positively associated with BW. In addition, we found that the relative expression levels of tight junction proteins (Claudin 1, Claudin 2, ZO-1 and ZO-2) in the high group showed an upward trend, although this trend was not significant (P > 0.05). The expression of pro-inflammatory factors (IL-1β, IL-2 and TNF-α) decreased in the high group, while the anti-inflammatory factor IL-10 increased. Of course, except IL-2, these differences were not significant (P > 0.05). Finally, the correlation analysis showed that Escherichia-Shigella was significantly positively correlated with IL-1β (P < 0.05). These findings may provide fundamental data for the development of next-generation probiotics and assist the development of strategies for changing the gut microbiota to promote the growth performance in the duck industry.